Ready or not : a novel - Bastone, Cara (The Dial Press, 2024)
"Eve Hatch is pretty content with her life. Her apartment in Brooklyn is cozy, but close to her childhood best friend Willa, and far from her midwestern, religious upbringing where she always felt misunderstood. While her position as an administrative assistant at the Wildlife Federation of America is a dream-adjacent job, she's hoping her passion and hard work will help her land a more glamorous role where she could actually make a difference someday. And sure, her most recent romantic history has consisted of not one but two disappointing men named Derek. At least she always knows what to expect...until she finds herself expecting after an uncharacteristic one-night-stand. Suddenly, this surprise pregnancy cracks open all the relationships in her life. Eve's ride-or-die friendship with Willa is suddenly feeling off. And surprisingly, it's Willa's steadfast older brother, Shep, who steps up to help. He has always been supportive, but now he's checking in, ordering her surprise lunches, listening to all her woes, and... is suddenly irresistible? Add in a kind but conflicted baby daddy--who also happens to have a girlfriend--and Eve is feeling out of her depth, to say the least. Over the course of nine months, as Eve struggles to figure out the next right step in her expanding reality, she begins to realize that love, in all forms, can sneak up on you when you least expect it"--